The role of Bank Muamalat leadership in improving employee service excellence - Ginanjar, Singgih; Nellitawati, Nellitawati; Wildanah, Fifin (Indonesian Institute for Counseling, Education and Theraphy, 2024)
The background of this research is still the need to improve the excellent service of Bank Muamalat Bengkulu. This study aims to analyze how the leadership role of Bank Muamalat Bengkulu in improving employee excellent service. The research design uses qualitative methods that are carried out based on guidelines in achieving research objectives. Data collection using observation and interviews with 34 employees as informants. Qualitative data was analyzed using Miles & Huberman's model technique. The research findings show that the leadership aspects of Bank Muamalat Bengkulu are at a good level and the aspects of improving the excellent service of Bank Muamalat Bengkulu are at a good level. This research also establishes the leadership role of Bank Muamalat Bengkulu in improving employee excellent service. Therefore, it is recommended that the leadership of Bank Muamalat Bengkulu carry out collaborative activities with employees and banking stakeholders in order to improve employee service excellence. Based on these results, the conclusion is that the leadership role of Bank Muamalat Bengkulu in improving employee service excellence can still be improved.